Representações sociais dos profissionais e mapeamento da rede de proteção e atendimento sobre violência contra a mulher em Porto Velho, Rondônia - Mendes, Melila Braga Alves e Silva (2020)
Violence against women is a serious problem that damages health and violates human rights, with serious consequences for women, family, and society. The services provided and professionals who work in the protection and service network are fundamental in helping, support and combating the problem. This research aimed to establish the mapping and flows of the protection and care network for women in situations of violence and to investigate the social representations of professionals working in the areas of security, justice, social assistance and health in Porto Velho, Rondônia. The thesis consists of two studies that covered the services available and professional performance in the capital. Study I aimed to establish the mapping of the main services available and flows of the care and protection network and to investigate the perceptions about the professionals’ network work. Twelve professionals working in the network participated in the study and the data were analyzed through Thematic Analysis. The results indicated progress in public policies, understanding of the importance of the network and the professional’s commitment to the situations of violence treated. Disarticulation between services, shortage of human resources in the face of high demand and lack of adequate training were also identified. The results can contribute to the improvement of the network. Study II sought to know and analyze the social representations of professionals about the role of women, the context of violence and public policies created to face the problem. Semi-structured interviews were conducted with 12 professionals working in the areas of security, justice, social assistance, and health. The data were analyzed through Thematic Analysis and Theory of Social Representations. The results pointed to representations based on gender inequality and prejudice about the role of women in the family and society, as well as blaming violence. The data indicated necessary changes and investments, such as the implementation of planned public policies and the need for training in the area. The information can contribute to the direction of actions relevant to the improvement of the work developed. In view of the complexity of the phenomenon of violence and the high rate in the region, the development of local studies can assist in the pertinent actions and decision making of the public power.